2021
DOI: 10.1177/13621688211001289
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in language learning: A systematic review of 20 years of research methods and definitions

Abstract: At the turn of the new millennium, in an article published in Language Teaching Research in 2000, Dörnyei and Kormos proposed that ‘active learner engagement is a key concern’ for all instructed language learning. Since then, language engagement research has increased exponentially. In this article, we present a systematic review of 20 years of language engagement research. To ensure robust coverage, we searched 21 major journals on second language acquisition (SLA) and applied linguistics and identified 112 r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(198 citation statements)
references
References 81 publications
8
189
0
1
Order By: Relevance
“…In addition to the notion of action, Hiver et al (2021b) identified three other characteristics of engagement, namely, that engagement is characterized by being highly dependent on context, having an object, and being dynamic and malleable. Previous research has been conducted at various levels, such as schools, classrooms, and specific tasks (Fredricks et al, 2004), and it has demonstrated that aspects of engagement vary depending on the context, such as students' sense of belonging in the classroom and their active participation within a specific task.…”
Section: Literature Review Student Engagement In the L2 Classroommentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the notion of action, Hiver et al (2021b) identified three other characteristics of engagement, namely, that engagement is characterized by being highly dependent on context, having an object, and being dynamic and malleable. Previous research has been conducted at various levels, such as schools, classrooms, and specific tasks (Fredricks et al, 2004), and it has demonstrated that aspects of engagement vary depending on the context, such as students' sense of belonging in the classroom and their active participation within a specific task.…”
Section: Literature Review Student Engagement In the L2 Classroommentioning
confidence: 99%
“…Students' active participation and involvement in schoolrelated activities and academic tasks have been defined as student engagement (Mercer & Dörnyei, 2020), and research on student engagement has received considerable attention in second language acquisition (SLA) research (Hiver et al, 2021a;Oga-Baldwin, 2019). Studies demonstrate that student engagement has been linked to active participation, task completion, time on task, persistence, enthusiasm, satisfaction, deeper learning, and improved academic achievement (Christenson et al, 2012;Hiver et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…The term engagement can be generally understood as the state of paying attention to perform a certain activity (Hiver et al, 2021b). In the educational realm, an engaged student can be defined as the one who exerts themselves to the process of learning (Guthrie et al, 1996;Hiver et al, 2021b).…”
Section: Definition Of Engagementmentioning
confidence: 99%
“…The term engagement can be generally understood as the state of paying attention to perform a certain activity (Hiver et al, 2021b). In the educational realm, an engaged student can be defined as the one who exerts themselves to the process of learning (Guthrie et al, 1996;Hiver et al, 2021b). As for how engagement is viewed at tertiary education, Coates (2007) argues: engagement is seen to comprise active and collaborative learning, participation in challenging academic activities, formative communication with academic staff, involvement in enriching educational experiences and feeling legitimated and supported by university learning communities.…”
Section: Definition Of Engagementmentioning
confidence: 99%
See 1 more Smart Citation